Actions That Obstacle The Justice Process (Contempt Of Court) in The Criminal Law System in Indonesia - H. Yusep Mulyana (East Asian Journal of Multidisciplinary Research, 2023)
In Law Number 1 of 2023 concerning the Criminal Code, especially Article 281, criminal acts against the court process (contempt of court) are punishable by imprisonment for a maximum of 1 year or a fine of up to 10 million rupiah. The actions included in the offense of contempt of court, among others, are aimed at anyone who: Does not comply with a court order or a judge's decision issued for the benefit of the judicial process. Being disrespectful to judges or the trial or attacking the integrity or impartiality of judges in court proceedings; or Unlawfully record, publish directly, or allow for publication anything that can affect the impartial nature of judges in court hearings. The environment of the court body must be able to become a legal institution that is trusted by the public. These events should be viewed from the perspective of the "consequences" that events could have had. Some of the public are of the opinion that sometimes courts are not really a place to seek and find justice. This assumption arose because of a number of previous events. For example, there were cases of judges and other court officials who were tried and convicted of accepting bribes. Another incident, there are arrears of cases that are not terminated in accordance with the principle of simple and fast. Therefore, it is important to strengthen public trust. This is to reduce the number of contempt of court and to foster the public's desire to maintain and protect the honor of the court and judges from all forms of harassment.